Prenatal developmental toxicity study of an alkaloid-free Ageratum conyzoides extract powder in rats by oral administration - Subah, Silma; Bogoda, Nathasha; Glávits, Róbert; Venkatesh, Ruchitha; Murbach, Timothy S.; Kolep-Csete, Kornélia (Regulatory toxicology and pharmacology, 2020)
A prenatal developmental toxicological study was conducted to evaluate the safety of an alkaloid-free Ageratum conyzoides extract powder administration on pregnant female Wistar rats and on the development of the conceptus in accordance with OECD test guideline (no. 414). Pyrrolizidine alkaloids (PAs) naturally present in A. conyzoides have been shown to induce toxicity in past studies, particularly towards hepatic cells. Therefore our test item preparation of A.conyzoides extract (aerial part of the plant) consisted of the removal of PAs. There were no treatment related adverse effects found during maternal examinations (body weights, food consumption, numbers of pregnant and non-pregnant female rats, endocrine evaluation, gravid uterine weights, and number of corpora lutea), maternal/fetal examinations (numbers of implantation sites, pre-and post-implantation loss (%), dead and live fetuses (%), resorption sites), or fetal examinations (litter size and weights, number of fetuses, sex ratio, or external, visceral, and skeletal variations and malformations) in the Ageratum conyzoides extract powder groups at doses of 500, 1000 and 2000 mg/kw bw/day compared to vehicle control group. The no observed adverse effect level (NOAEL) determined for both maternal and developmental toxicity was 2000 mg/kg bw/day, which was the highest dose tested. •Toxicity of A.conyzoides has been postulated due to pyrrolizidine alkaloids.•The test item was an alkaloid-free ethanolic extract of A.conyzoides.•No treatment related maternal or fetal adverse effects of A.conyzoides extract were observed in rats.•The NOAEL for maternal and developmental toxicity was 2000 mg/kg bw/day, the highest dose tested.•This is the first study investigating the prenatal developmental toxicity of A.conyzoides in rats.